On Minkowski and Hermite-Hadamard integral inequalities via fractional integration - Dahmani, Zoubir (Annals of Functional Analysis, 2010)
In this paper, we use the the Riemann–Liouville fractional inte- gral to develop some new results related to the Hermite–Hadamard inequality. Other integral inequalities related to the Minkowsky inequality are also es- tablished. Our results have some relationships with [E. Set, M. E. Ozdemir and S.S. Dragomir, J. Inequal. Appl. 2010 , Art. ID 148102, 9 pp.] and [L. Bougoffa, J. Inequal. Pure and Appl. Math. 7 (2006), no. 2, Article 60, 3 pp.]. Some interested inequalities of these references can be deduced as some special cases.
Keywords: Concave function, Hermite–Hadamard inequality, Minkowski in- equality, Riemann–Liouville fractional integral.